Plasma concentrations of secretory leukocyte protease inhibitor (SLPI) differ depending on etiology and severity in community-onset bloodstream infection - Lange, Anna; Cajander, Sara; Magnuson, Anders; Sundén-Cullberg, Jonas; Strålin, Kristoffer; Hultgren, Olof (European journal of clinical microbiology & infectious diseases, 2019)
The severity of bloodstream infections (BSI) depends on pathogen, source, and host factors. Secretory leukocyte protease inhibitor (SLPI) counteracts tissue damage, balances inflammation, and is increased in pneumonia and sepsis. We aimed to evaluate whether SLPI production differs depending on etiology, disease severity, and sex in BSI and to correlate SLPI with markers of inflammation and immunosuppression. Of the adult patients with BSI, 109 were included and sampled repeatedly, from hospital admission through day 28. Controls (blood donors) were sampled twice. SLPI in plasma was measured with enzyme-linked immunosorbent assay (ELISA) technique. Streptococcus pneumoniae and Staphylococcus aureus etiology were associated with higher SLPI than Escherichia coli on days 1–2 and 3. On day 1–2, subjects with sepsis had higher SLPI concentrations than those with non-septic BSI. Pneumonia was associated with higher SLPI than a non-pulmonary source of infection. SLPI co-varied with inflammatory markers. SLPI concentrations did not differ with regard to sex in the full cohort, but men with pneumonia had higher SLPI than women on day 1–2. S. pneumoniae and S. aureus BSI were associated with higher SLPI, when compared to E. coli . Severity and pneumonia, as well as male sex in the pneumonia sub-cohort, were factors independently associated with higher SLPI.